COMPETITIVENESS IN PHARMACEUTICAL INDUSTRY: PARTICIPANTS IN SUPPLY SIDE AND DEMAND SIDE - Filipova, Milena; Nedelcheva, Yulia (Revista Inclusiones, 2020)
The objective of the article is to explore the competitiveness of the pharmaceutical industry through supply and demand participants. We establish that the state policy for prioritizing the interests of the participants creates a temporary situation (a quasi-balance) called competitiveness. The regulatory authority plays a leading role in competitiveness by seeking the center of gravity of participants’ interests. The results of the article indicate that participants have multiple roles. Particular attention has been paid to the State and its involvement in both the supply side and demand side of pharmaceutical products. The State’s participation in competition in the pharmaceutical industry must be reduced and directed at the competitiveness of the State.